Penyuluhan Pra Nikah untuk Mengurangi Angka Perceraian - Didit Darmawan; Asnal Mala; Budi Handayani; Budi Purwantiningsih; Hanik Yuni Alfiyah; Hermawan Hermawan; Rahmat Ihya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
To create a strong country, the people in that country must be strong and solid. A strong society can be created by building a harmonious family, in Indonesia the divorce rate is increasing, especially in marriages that occur at a young age. To reduce this, it is necessary to carry out pre-marital counseling for people of marriageable age. Counseling can be done through Community Service (PkM) activities. The PkM team from Sunan Giri University in Surabaya carried out PkM activities by providing pre-marital counseling to reduce the divorce rate in Buncitan Village, Sidoarjo. There were 25 participants who took part in the extension activities. PkM activities are carried out according to plan and can run well. PkM activities are carried out to foster good relations between Sunan Giri University in Surabaya and the community. In addition, PkM activities are a form of participation in harmonious community development.